Exploring oral health indicators, oral health-related quality of life and nutritional aspects in 23 medicated patients from a short-term psychiatric ward - Frigaard, Julie; Hynne, Håvard; Randsborg, Karoline; Mellin-Olsen, Tonje; Young, Alix; Rykke, Morten; Singh, Preet Bano; Hove, Lene Hystad; Hofgaard, Anne Kristine; Jensen, Janicke Liaaen (Frontiers in Public Health, 2023)
Patients suffering from psychiatric disorders face many difficulties due to their condition, medications and lifestyle. Oral health and nutrition may be affected, further complicating their lives. Our aim was to provide in-depth information on oral health and nutritional factors in a small group of patients in short-term psychiatric ward. Twenty-three patients (mean age 36, average medications five) were recruited during short-term hospitalization in a psychiatric ward. Inclusion criteria: anxiety, psychosis and/or depression, and use of at least one antidepressant or anxiolytic/antipsychotic drug with xerostomia as a known side effect. Subjective oral dryness was evaluated using the Shortened Xerostomia Inventory (SXI). Oral examination included Clinical Oral Dryness Score (CODS), secretion of unstimulated (UWS) and stimulated whole saliva (SWS), and evaluation of dental, gingival, and periodontal status. Self-reported complaints of oral disorders were recorded. The Oral Health Impact Profile-14 (OHIP-14) was used to explore oral health-related quality of life. Nutritional status was assessed using the Patient-Generated Subjective Global Assessment Short Form (PG-SGA-SF), and diet quality was assessed using the Mediterranean diet score (KIDMED). Compared to healthy controls, the patients had significantly higher SXI scores and CODS, and SWS secretion was lower. Complaints of dysgeusia and halitosis were significantly more frequent among patients. Gingivitis was more common in patients. OHIP-14 scores were much higher in the patients, and they reported significantly poorer oral- and general health. Most patients lacked a regular meal pattern. Very low diet quality was observed in five patients, while improvements were needed in twelve. “Dry mouth” and “No appetite, just did not feel like eating” were the most common symptoms preventing patients from eating enough. The PG-SGA-SF symptoms component score showed a strong negative correlation with self-reported oral health, and a strong positive correlation with OHIP-14. This relatively small group of patients in short-term psychiatric ward had both reduced oral health and poor oral health-related quality of life. Furthermore, their nutritional intake was affected by their oral health problems. Although larger groups need to be studied, these findings indicate that oral health and nutrition should be evaluated and adjusted in these patients to improve their overall care.